2022
DOI: 10.3389/fcimb.2022.860526
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cytokine Levels Assist in the Diagnosis of Respiratory Bacterial Infections or Concurrent Bacteremia in Patients With Non-Hodgkin’s Lymphoma

Abstract: Non-Hodgkin’s lymphoma (NHL) is a form of tumor that originates in the lymphoid tissues. Bacterial infections are very common in NHL patients. Because most of the patients do not experience apparent symptoms during the initial stage of infection, it is difficult to detect the underlying condition before it progresses to a more critical level. The activation of the cytokines is a hallmark of inflammation. Due to the advantages of short detection time and high sensitivity of cytokines, many studies have focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
4
6
1
Order By: Relevance
“…Our results revealed that IL-10, IL-8, IL-6, IFN-, IL-17A, and IL-17F levels in patients with bacterial lung illness were abnormally higher than those without infection (Table 2 ). This is different from our study on non-Hodgkin's lymphoma, where only IL-6, IL-8, IL-10, and IFN-γ have intersection indicators, while non-Hodgkin’s lymphoma Abnormal TNF-β is also present 11 . These differences may be primarily due to the disease itself, e.g., TNF-β can be related to tumor burden 20 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results revealed that IL-10, IL-8, IL-6, IFN-, IL-17A, and IL-17F levels in patients with bacterial lung illness were abnormally higher than those without infection (Table 2 ). This is different from our study on non-Hodgkin's lymphoma, where only IL-6, IL-8, IL-10, and IFN-γ have intersection indicators, while non-Hodgkin’s lymphoma Abnormal TNF-β is also present 11 . These differences may be primarily due to the disease itself, e.g., TNF-β can be related to tumor burden 20 .…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with lymphoma and other reports, IL-6 was the most dominant of all markers 11 , 18 , 19 ; our findings provide insight into the availability of IL-6 in AA for predicting bacterial lung infection. Our results revealed that IL-10, IL-8, IL-6, IFN-, IL-17A, and IL-17F levels in patients with bacterial lung illness were abnormally higher than those without infection (Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A previous study observed elevated levels of IL-6, IL-8, and IL-10 in newly diagnosed hematological malignancies accompanied by pulmonary bacterial infections [ 13 ]. Non-Hodgkin's lymphoma was analyzed separately, finding significantly raised levels of IL-6 (AUC = 0.92) in this disease [ 12 ]. The current study found that, apart from IL-6, changes in IL-8 levels exceeded those of PCT and CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that COVID-19 infection in elderly vulnerable patients to a cytokine storm, characterized by severe systemic elevation of several proinflammatory cytokines. Similarly, some studies have also observed raised cytokine levels in patients (both adults and children) with hematological malignancies, community-acquired pneumonia, and non-Hodgkin's lymphoma, and reported that cytokine levels have greater diagnostic sensitivity than both PCT and CRP [ 12 15 ]. Although previous studies have demonstrated that cytokines can predict infection in patients with hematological malignancies, these conditions differ markedly in both pathogenesis and immune characteristics, and cytokine production may also be affected by drug therapy.…”
Section: Introductionmentioning
confidence: 99%